A confiança interorganizacional nas compras - Tacconi, Marli de Fátima Ferraz da Silva (2012)
This research is part of the field of organizational studies, focusing on organizational purchase behavior and, specifically, trust interorganizational at the purchases. This topic is current and relevant by addressing the development of good relations between buyer-supplier that increases the exchange of information, increases the length of relationship, reduces the hierarchical controls and improves performance. Furthermore, although there is a vast literature on trust, the scientific work that deal specifically at the trust interorganizational still need further research to synthesize and validate the variables that generate this phenomenon. In this sense, this investigation is to explain the antecedents of trust interorganizational by the relationship between the variable operational performance, organizational characteristics, shared values and interpersonal relationships on purchases by manufacturing industries, in order to develop a robust literature, most consensual, that includes the current sociological and economic, considering the effect of interpersonal relationships in this phenomenon. This proposal is configured in a new vision of the antecedents of interorganizational trust, described as significant quantitative from models Morgan and Hunt (1994), Doney and Cannon (1997), Zhao and Cavusgil (2006) and Nyaga, Whipple, Lynch (2011), as well as qualitative analysis of Tacconi et al. (2011). With regard to methodological aspects, the study assumes the form of a descriptive, survey type, and causal trace theoretical and empirical. As for his nature, the investigation, explicative character, has developed a quantitative approach with the use of exploratory factor analysis and structural equation modeling SEM, with the use of IBM software SPSS Amos 18.0, using the method of maximum verisimilitude, and supported by technical bootstraping. The unit of analysis was the buyer-supplier relationship, in which the object under investigation was the supplier organization in view of the purchasing company. 237 valid questionnaires were collected among key informants, using a simple random sampling developed in manufacturing industries (SIC 10-33), located in the city of Natal and in the region of Natal. The first results of descriptive analysis demonstrate the phenomenon of interorganizational trust, in which purchasing firms believe, feel secure about the supplier. This demonstration showed high levels of intensity, predominantly among the vendors that supply the company with materials that are used directly in the production process. The exploratory and confirmatory factor analysis, performed on each variable alone, generated a set of observable and unobservable variables more consistent, giving rise to a model, that needed to be further specified. This again specify model consists of trajectories was positive, with a good fit, with a composite reliability and variance extracted satisfactory, and demonstrates convergent and discriminant validity, in which the factor loadings are significant and strong explanatory power. Given the findings that reinforce the model again specify data, suggesting a high probability that this model may be more suited for the study population, the results support the explanation that interorganizational trust depends on purchases directly from interpersonal relationships, sharing value and operating performance and indirectly of personal relationships, social networks, organizational characteristics, physical and relational aspect of performance. It is concluded that this trust can be explained by a set of interactions between these three determinants, where the focus is on interpersonal relationships, with the largest path coefficient for the factor under study